Continuous Delivery Pipelines for Teaching Agile and Developing Software Engineering Skills - (:unkn) unknown (© 2018 MECS, 2018)
The differences between academy and industry when it comes to working settings (schedules, workload, working environments, etc.), have motivated the development of a significant body of research on how to achieve meaningful learning processes of Software Development Life Cycles (SDLC) in the former, in order to ease the incorporation processes of new Software Engineers in the latter. Such research works have evolved together with the SDLC themselves, in particular between the early 2000s when most programs taught highly prescriptive methodologies like RUP/UP or Extreme Programming (XP) [1, 2, 3], and a decade later, when agile SDLC like SCRUM had already become one of the most widespread agile methodologies in the industry and academia slowly began to embrace it (near 100 references in Google Scholar for "teaching agile software development" between 2010 and 2017).

Las diferencias entre la academia y la industria en cuanto a los entornos de trabajo (horarios, carga de trabajo, ambientes de trabajo, etc.), han motivado el desarrollo de un importante cuerpo de investigación sobre cómo lograr procesos de aprendizaje significativo de los Ciclos de Vida de Desarrollo de Software (SDLC) en los primeros, con el fin de facilitar los procesos de incorporación de nuevos Ingenieros de Software en los segundos. Dichos trabajos de investigación han evolucionado junto con el propio SDLC, en particular entre principios de la década de 2000, cuando la mayoría de los programas enseñaban metodologías altamente prescriptivas como RUP/UP o Extreme Programming (XP) [1, 2, 3], y una década más tarde, cuando el SDLC ágil como SCRUM ya se había convertido en una de las metodologías ágiles más extendidas en la industria y la academia comenzó a adoptarla lentamente (cerca de 100 referencias en Google Scholar para "enseñar desarrollo de software ágil" entre 2010 y 2017).
Keywords: Ingeniería de software; Enseñanza ágil; Enseñanza SDLC; Software Engineering; Agile Teaching; Software Engineering Education; SDLC Teaching